Bioarchaeological studies of life in the age of agriculture : a view from the Southeast - Lambert, Patricia M., 1958- (Tuscaloosa : University of Alabama Press, 2000)
Annotation Investigations of skeletal remains from key archaeological sites reveal new data and offer insights on prehistoric life and health in theSoutheast. The shift from foraging to farming had important health consequences for prehistoric peoples, but variations in health existedwithin communities that had made this transition. This new collection draws on the rich bioarchaeological record of the Southeastern United Statesto explore variability in health and behavior within the age of agriculture. It offers new perspectives on human adaptation to various geographic andcultural landscapes across the entire Southeast, from Texas to Virginia, and presents new data from both classic and little-known sites. The contributors question the reliance on simple cause-and-effect relationships in human health and behavior by addressing such key bioarchaeological issues as disease history and epidemiology, dietary composition and sufficiency, workload stress, patterns of violence, mortuary practices, and biological consequences of European contact. They also advance our understanding of agriculture by showing that uses of maize were more varied than has been previously supposed. Representing some of the best work being done today by physical anthropologists, this volume provides new insights into human adaptation for both archaeologists and osteologists. It attests to the heterogeneous character of Southeastern societies during the late prehistoric and early historic periods while effectively detailing the many factors that have shaped biocultural evolution. Contributors include: Patricia S. Bridges, Elizabeth Monaham Driscoll, Debra L. Gold, Dale L. Hutchinson, Keith P. Jacobi, Patricia M. Lambert, Clark Spencer Larsen, Lynette Norr, Mary Lucas Powell, Marianne Reeves, Lisa Sattenspiel, Margaret J. Schoeninger, Mark R. Schurr, Leslie E. Sering, David S. Weaver, and Matthew A. Williamson.
1. Introduction / Patricia M. Lambert -- 2. Ancient diseases, modern perspectives : treponematosis and tuberculosis in the age of agriculture / Mary Lucas Powell -- 3. Warfare-related trauma in the late prehistory of Alabama / Patricia S. Bridges, Keith P. Jacobi, Mary Lucas Powell -- 4. Transitions at Moundville : a question of collapse / Margaret J. Schoeninger, Lisa Sattenspiel, Mark R. Schurr -- 5. Dental health at early historic Fusihatchee Town : biocultural implications of contact in Alabama / Marianne Reeves -- 6. Agricultural melodies and alternative harmonies in Florida and Georgia / Dale L. Hutchinson, Clark Spencer Larsen, Lynette Norr, Margaret J. Schoeninger -- 7. Inferring iron-deficiency anemia from human skeletal remains : the case of the Georgia Bight / Clark Spencer Larsen, Leslie E. Sering -- 8. A comparison of degenerative joint disease between upland and coastal prehistoric agriculturalists from Georgia / Matthew A. Williamson -- 9. Dental health and Late Woodland subsistence in coastal North Carolina / Elizabeth Monahan Driscoll, David S. Weaver -- 10. Life on the periphery : health in farming communities of interior North Carolina and Virginia / Patricia M. Lambert -- 11. "Utmost confusion" reconsidered : bioarchaeology and secondary burial in late prehistoric interior Virginia / Debra L. Gold.
Includes bibliographical references (pages 219-272) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Indians of North America -- Southern States -- Antiquities -- Congresses; Indians of North America -- Health and hygiene -- Southern States -- Congresses; Indians of North America -- Anthropometry -- Southern States -- Congresses; Mississippian culture -- Congresses; Southern States -- Antiquities -- Congresses; Physical anthropology; Indians of North America -- Southern States -- Antiquities -- Congresses; Mississippian culture -- Congresses; Southern States -- Antiquities -- Congresses; Indigenous peoples -- Anthropometry -- Southern States -- Congresses; Medicine, Ancient; Indians -- Health and hygiene -- Southern States -- Congresses; Indians, North American -- history; Agriculture -- history; Anthropology, Physical; Diet -- history; Health Status; History, Ancient; Southeastern United States; Peuples autochtones -- États-Unis (Sud) -- Antiquités -- Congrès.; Peuples autochtones -- Santé et hygiène -- États-Unis (Sud) -- Congrès.; Autochtones -- Anthropométrie -- États-Unis (Sud) -- Congrès.; Culture du Mississippi -- Congrès.; États-Unis (Sud) -- Antiquités -- Congrès.; Peuples autochtones -- États-Unis (Sud) -- Antiquités -- Congrès.; Culture du Mississippi -- Congrès.; États-Unis (Sud) -- Antiquités -- Congrès.; Anthropologie physique; Médecine ancienne; physical anthropology; MEDICAL -- Health Risk Assessment; MEDICAL -- Epidemiology; Physical anthropology; Antiquities; Indians of North America -- Anthropometry; Indians of North America -- Antiquities; Indians of North America -- Health and hygiene; Mississippian culture; Southern States; Indiens -- États-Unis (sud) -- Antiquités -- Congrès.; Indiens -- États-Unis (sud) -- Santé et hygiène -- Congrès.; Indiens -- États-Unis (sud) -- Anthropométrie -- Congrès.; États-Unis (sud) -- Antiquités -- Congrès.; Congress; proceedings (reports); Conference papers and proceedings; Electronic books; Conference papers and proceedings; Actes de congrès.